2001
DOI: 10.1017/s1355838201002308
|View full text |Cite
|
Sign up to set email alerts
|

A conserved pseudouridine modification in eukaryotic U2 snRNA induces a change in branch-site architecture

Abstract: The removal of noncoding sequences (introns) from eukaryotic precursor mRNA is catalyzed by the spliceosome, a dynamic assembly involving specific and sequential RNA-RNA and RNA-protein interactions. An essential RNA-RNA pairing between the U2 small nuclear (sn)RNA and a complementary consensus sequence of the intron, called the branch site, results in positioning of the 29OH of an unpaired intron adenosine residue to initiate nucleophilic attack in the first step of splicing. To understand the structural feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
98
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(111 citation statements)
references
References 41 publications
12
98
1
Order By: Relevance
“…[36,37] NMR structural analyses have shown that this Ψ is responsible for an extrahelical positioning of the branch adenosine in the isolated branch helix. [35,38] Although no Ψ has been identified in group II introns to date, the relationship with the spliceosome makes a bulged-out adenosine in context of the whole group II intron also tempting to propose. However, in the light of the many differences between the two systems and the here presented solution structure of an active D6 construct, the occurrence of a helically stacked branch adenosine should be considered more closely.…”
Section: Discussionmentioning
confidence: 99%
“…[36,37] NMR structural analyses have shown that this Ψ is responsible for an extrahelical positioning of the branch adenosine in the isolated branch helix. [35,38] Although no Ψ has been identified in group II introns to date, the relationship with the spliceosome makes a bulged-out adenosine in context of the whole group II intron also tempting to propose. However, in the light of the many differences between the two systems and the here presented solution structure of an active D6 construct, the occurrence of a helically stacked branch adenosine should be considered more closely.…”
Section: Discussionmentioning
confidence: 99%
“…Pseudouridine is known to affect the structure of tRNAs, affecting base-stacking (5) in the anticodon loop, and when it appears in stems or the anticodon, it strengthens base-pairing (6,(32)(33)(34). When modeled with RNA oligomers, the presence of ⌿ in U2 small nuclear RNA causes a change in the structure of the lariat branch point of pre-messenger RNA (35,36). A functional requirement for ⌿ in U2 small nuclear RNA has also been shown in reconstitution of splicing systems (37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…NMR measurements indicated that these effects then propagated throughout the helix, indicating that pseudouridine has an intrinsic ability to stabilize RNA-RNA base-pairing interactions. In the context of the base-pairing interaction between the pre-mRNA branch site and the U2 branch site recognition region, Newby and Greenbaum have shown that pseudouridine indeed enhances pairing affinity (Newby and Greenbaum, 2001). Taken together, it is conceivable that all these features of pseudouridine, including its ability to alter structure, increase base-stacking, and improve RNA-RNA base-pairing, contribute to the function of splicesomal snRNAs in splicing.…”
Section: Pseudouridine Differs From Its Counterpart Uridine In Severalmentioning
confidence: 99%